(untitled) (Plant Tissue Culture and Biotechnology, 2016)
The study was conducted to develop micropropagation and slow?growth conservation protocol for endangered relict plant species Campanula sclerophylla. The best multiplication rate up to 7.2 shoots per explant was obtained on half strength MS supplemented with 3 mg/l BAP and 1 mg/l IAA. The effects of temperature/light conditions, sorbitol and ABA on shoot growth of Campanula sclerophylla were studied. Addition of 3 g/l sorbitol and 5 mg/l ABA inhibited shoot length and multiplication of C. sclerophylla. Explants were stored for 9 months without subculture at 7º? and light intensity of 23 lux. Plant Tissue Cult. & Biotech. 26(2): 143-149, 2016 (December)